Using GerdQ as a screening diagnostic method in children with gastroduodenal diseases - N.V. Pavlenko; K.V. Voloshyn; O.L. Slobodianiuk; L.G. Voloshyna; O.B. Hanzii (Zaslavsky O.Yu., 2018)
Background. Problem of screening for esophageal diseases in primary stages of diagnosis in children with gastroduodenal pathology is widespread. As non-invasive and economically available method, a modified Gastroesophageal Reflux Disease Questionnaire (GerdQ) is proposed for children aged 12-18 years. The purpose of the study is comparative analysis of the state of esophageal, gastric and duodenal mucosa and endoscopic pH values of the esophagus with the results of GerdQ use in children with gastroduodenal pathology. Materials and methods. Sixty seven children aged 12-18 years were examined. All patients underwent endoscopic study of the esophagus, stomach and duodenum with endoscopic pH measuring. The GerdQ was filled out by the children surveyed. Results. The data obtained indicate a significantly higher incidence of catarrhal and erosive esophagitis in children with destructive and catarrhal changes in the gastric mucosa and duodenum. The degree of gastroesophageal reflux and a decrease in pH values in the esophagus and stomach progressed in the presence of significant changes in the gastric mucosa. GerdQ results indicated GERD in patients with score ≥ 8. Endoscopy findings in this group were mostly catarrhal and destructive changes of esophageal mucosa with high acidity. Patients with score < 8 had mostly motility disorders (gastroesophageal reflux) and moderate increase of acidity. The results of GerdQ comparison with the data of the endoscopic study and the pH-measuring shows a significant (95 %; p < 0.05) coincidence of positive GerdQ results with pronounced endoscopic changes in the esophageal mucosa and a decrease in pH < 4 in the esophagus and < 1.2 in the stomach. Conclusions. The study shows that the sensitivity of the questionnaire is quite high and allows its use at the primary stage of diagnosis in children of middle and senior school age.